DEVELOPING STUDENTS’ CLINICAL SKILLS BASED ON INNOVATIVE PEDAGOGICAL APPROACHES IN MEDICAL EDUCATION - Mahsudov Valijon Gafurjonovich (TADQIQOTLAR, 2026)
Abstract. This article analyzes the issues of forming students’ clinical skills based on innovative pedagogical approaches in the medical education system. It is argued that the introduction of modern educational technologies, in particular, simulation learning, problem-based learning (PBL), case-study and interactive methods into the educational process serves to integrate students’ theoretical knowledge with practice. It is also shown that through these approaches, students acquire the skills of clinical thinking, diagnosis, correct decision-making and effective communication with the patient. The results of the study confirm the importance of innovative pedagogical methods in improving the quality of medical education and training competitive, highly qualified specialists.